Time-resolved cell-to-cell heterogeneity of Listeria innocua after nisin exposure - Fante, Niklas; Desiderato, Christian K.; Riedel, Christian U.; Grünberger, Alexander (Frontiers in Bioengineering and Biotechnology, 2024)
The use of bacteriocins is a promising approach for addressing the immense threat of food-borne and drug-resistant pathogens. In recent years screening platforms for novel bacteriocins using whole-cell biosensors have been established. During screening cell-to-cell heterogeneity is currently neglected but might play a crucial role in signal development of the whole-cell biosensor after bacteriocin exposure. In this study, we explored the temporal dynamics of the signal heterogeneity of the biosensor Listeria innocua LMG2785/pNZpHin2Lm after nisin exposure using microfluidic single-cell analysis. The results provided novel and detailed insights into the dynamics of cell-to-cell heterogeneity in L. innocua LMG2785/pNZpHin2Lm at different nisin concentrations with a high spatio-temporal resolution. Furthermore, the formation of subpopulations during bacteriocin exposure was observed. In-depth single-cell tracking even revealed the regeneration of disrupted cells and recovery of pH homeostasis in rare instances. These findings are highly important for the future design and execution of bacteriocin assays and for the interpretation of fluorescence signal development at the population level after exposure to different concentrations of bacteriocins (here, nisin), as well as for obtaining deeper insights into single-cell persistence strategies to quantify the efficacy and efficiency of novel bacteriocins.